2008
DOI: 10.1016/j.dental.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water content and initiator composition on photopolymerization of a model BisGMA/HEMA resin

Abstract: Aims-The purpose of this study was to evaluate the effects of photoinitiator type and water content on the polymerization rate (R p ) and degree of conversion (DC) of a model BisGMA/HEMA-based resin.Materials and methods-The comonomer mixture consisted of BisGMA/HEMA (60/40 by weight). Different two-or three-component photoinitiator systems were incorporated. Twocomponent systems were 0.5% CQ (camphorquinone) and 0.5% DMAEMA (2-(dimethylamino) ethyl methacrylate) or 0.5% CQ and 0.5% 4E (Ethyl 4-dimethylaminobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 25 publications
6
91
0
10
Order By: Relevance
“…3) are typical for photoinitiated polymerization (Guo et al 2008;Ye et al 2009;Liu and Wang 2013). The close resemblance in plateau DC regardless of 4E's presence (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…3) are typical for photoinitiated polymerization (Guo et al 2008;Ye et al 2009;Liu and Wang 2013). The close resemblance in plateau DC regardless of 4E's presence (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have shown that in the presence of water, Bis-GMA/HEMA undergoes microphase separation, the hydrophilic tertiary amine and hydrophobic camphoroquinone tend to exist in the hydrophilic HEMA phase and hydrophobic Bis-GMA phase, respectively. 23,24 This decreases the chance of their coming into contact; therefore, fewer radicals will be generated and a lower degree of conversion could be found in the Ketac N100 matrix than in Vitremer matrix. Moreover, Vitremer shows a third polymerization setting reaction that ensures that any HEMA not polymerized by irradiation will set.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in absorbance ratios of 1637 cm -1 /1608 cm -1 were monitored and DC could be calculated by using the following equation: [11,12] …”
Section: Measurement Of Degree Of Conversionmentioning
confidence: 99%